A study on seroprevalence of hepatotropic viruses among HIV-positive individuals attending the integrated counselling and testing centre (ICTC) in Mayo hospital of Nagpur city, Maharashtra, India - Sherwani, Nikita; Khadse, R. K.; Bhawnani, Dhiraj; Verma, Nirmal (International Journal of Research in Medical Sciences, 2017)
Background: Infection with human immunodeficiency virus type-1 and its end stage, acquired immunodeficiency syndrome is the major public health challenge of modern time. A variety of exogenously acquired infectious agents appear to influence the pace of HIV replication, the destruction of CD4+ T cells, and HIV transmission to infants and sexual partners. More persistent elevations in plasma HIV levels have been seen in patients with chronic infections (such as those with tuberculosis and herpes and hepatitis viruses), and such co-infected patients have a more rapid loss of CD4+ T cells and an increased rate of progression to AIDS and death. Within India, variable co-infection rates have been reported from region to region. With the above background, the present study was undertaken to study the seroprevalence of hepatotropic viruses (Hepatitis B virus and Hepatitis C virus) in HIV-positive individuals attending the Integrated Counselling and Testing Centre (ICTC) in Mayo hospital of Nagpur city, Maharashtra, India. Methods: The current prospective study was conducted in the department of microbiology, Indira Gandhi government medical college and Mayo general hospital, Nagpur (Maharashtra) from August 2005 to August 2007. All the patients attending ICTC were included in the study. 300 HIV negative matched controls were also included in the study. All the individuals who were positive for HIV infection were selected for this study and further tested for the presence of hepatitis B surface antigen (HBsAg) and anti-HCV antibodies. Data was compiled in MS excel. Then it was analyzed using online statistical calculator and chi square test were applied with value of P <0.05 was considered statistically significant for interpretation of finding. Results: Maximum numbers of HIV positive patients (38.8%) were in age group of 31-40 years. Present study showed male preponderance in HIV positive patients. Males showed a slightly high seroprevalence of HBsAg (9.21%) compared to females (7.57%) among HIV positive patients. The difference in positivity of two viral agents studied in HIV positive patients was highly significant as compared to HIV-negative individuals (P <0.001). Conclusion: On the basis of the findings that the co-infection of hepatotropic viruses (HBV and HCV) were significantly higher in HIV positive cases than controls, the study concludes that the chronic viral hepatitis is a serious concern in HIV-infected patients. Thus, there is an urgent need to ensure the screening of the same in HIV-infected patients.